The Influence of Classroom Environment on Students Academic Performance in Secondary Schools within the Bamenda II Municipality, North West Region - Cameroon - Ambei , Moses Chu; Tata , Easter (American Journal of Education and Practice, 2022)
Purpose: This paper investigated the influence of classroom environment on the academic performance of students in secondary schools within the Bamenda II Municipality. More specifically, this study investigated the influence of classroom environment on the academic performance of students in secondary schools within the Bamenda II, Mezam Division of the North West Region of Cameroon. Methodology: One hundred and sixty two (162) students were sampled across three secondary schools to get their opinion on the issue under investigation. A cross-sectional survey research design was used and the sample of the study emerged through a simple random and convenient sampling techniques. A questionnaire was administered on the respondents. The questionnaires were analyzed based on the research hypothesis. Findings: The findings indicated that the classroom environment has a significant influence on the academic performance of the students. Recommendation: From the findings, it was recommended that; corporate organizations and individuals should be encouraged by the schools to donate generously in cash and kind for the provision of staff educational development and construction of more classes.